Implementation of Al-Qur'an Values on Bees and Honey by Trigona Itama Bee Farmers: A Living Qur'an Study in Palangka Raya - Harin Putriani; Arif Firdausi Nur Romadlon; Edy Wirastho; Nisrun Latifah (Jurnal test, 2025)
This study aims to describe the understanding and implementation of the Qur'anic verses about bees and honey, specifically Surah An-Nahl verses 68–69, by Trigona Itama beekeepers in Sei Gohong Village, Palangka Raya. This research employs a qualitative descriptive method, with data collection techniques including direct observation, interviews, and field documentation. The results show that the beekeepers understand and implement the Qur'anic verses about bees and honey as a guide for their beekeeping activities, not merely as religious knowledge. They apply this understanding by constructing beehives, selecting locations that support the ecosystem, providing natural food sources, harvesting honey properly, and sharing knowledge with the community. This study contributes new insights to the field of Living Qur'an studies, particularly on how the Qur'anic verses about nature can be applied in real-life practices. It is hoped that these findings can inspire the development of similar initiatives in other regions and open opportunities for further research on the application of Qur'anic verses in community life.